Paper-based high-performance environment-friendly coating material and preparation method thereof
By adjusting the pH value of the nanocellulose solution and blending it with the pulp fibers and dehydrating it, the processing technology of paper-based materials is simplified, the problems of insufficient performance and high energy consumption in traditional processes are solved, and the preparation of high-performance environmentally friendly coating materials is realized.
Patent Information
- Application Number
- CN202510372926.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
Existing paper-based materials have shortcomings in mechanical properties and barrier properties, especially in poor performance after being wet, and the traditional processing technology is complex and energy-consuming, which affects environmental protection characteristics.
By adjusting the pH value of the nanocellulose solution to 6.5~7.5, blending it with the diluted pulp fibers and dehydrating it, a high-performance environmentally friendly coating material is directly obtained. This method simplifies the process flow, avoids multiple rounds of coating and drying processes in traditional processes, and reduces energy consumption.
It has achieved improvements in the mechanical properties and barrier properties of paper-based materials, while simplified processing technology, reduced energy consumption, and maintained environmentally friendly characteristics.
Smart Images

Figure CN119877315A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a paper-based material, and in particular to a paper-based high-performance environmentally friendly coating material and a preparation method thereof. Background Art
[0002] Food packaging provides protection for food from physical, chemical and biological changes. Currently, petroleum-based plastics are still the main materials used in the market. Although petroleum-based plastics have the advantages of low cost, light weight, strong durability and excellent barrier properties, they have a short service life and generate a lot of pollution during recycling, becoming one of the improperly handled wastes. As an alternative, paper-based materials have the advantages of sustainable resource sources, biodegradability and recyclability, but their barrier properties and mechanical properties are poor, especially after being wetted, which is mainly attributed to the hydrophilic nature of its main component, plant fibers, as well as the porous internal structure and rough surface. To achieve its wide application in the market, it is usually necessary to use post-processing processes such as hot pressing or lamination, coating or integration with other materials (such as polymer additives, plastic films or silicon / fluorine coatings), which may affect its environmental characteristics.
[0003] In recent years, the sustainability and excellent performance of nanocellulose (CNFs) have attracted great attention. Nanocellulose is the smallest structural unit extracted from plant cell walls. It is a fiber with a diameter of less than 20 nm, a length of 200 nm to several microns, and an aspect ratio greater than 150. It has the advantages of biodegradability, excellent mechanical properties, high film-forming properties, and surface modifiability. Pure CNF film after hot pressing has dense stacking, almost zero porosity, and certain hydrophobicity, thus showing excellent barrier properties. Therefore, the existing technology has used nanocellulose as a coating on paper substrates in food packaging applications.
[0004] Most traditional processes still use rod coating, spray coating or dip coating technology to apply CNF as a coating for paper-based materials. For example, Chinese patent CN107524043A proposes a laminated reinforced paper base and its preparation method and application, which repeatedly assembles nanofiber coatings layer by layer to stack and alternately stack on pulp fibers, making the fiber surface structure complex and thus obtaining a reinforced paper base. Such processing technology still faces three major challenges: 1) High requirements for CNF viscosity and concentration; 2) Multiple rounds of coating are required, resulting in complex processing procedures; 3) It is difficult to ensure uniform and stable high-quality coatings; 4) Multiple rounds of drying are required subsequently, resulting in excessive energy consumption. In addition, high moisture content during the drying process may cause poor shrinkage of the paper substrate, thereby affecting the mechanical properties.
[0005] In summary, how to improve the mechanical properties and barrier properties of pulp materials while simplifying the processing technology is a huge difficulty and challenge in the field of high-performance paper-based material processing. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a paper-based high-performance environmentally friendly coating, to prepare a paper-based high-performance environmentally friendly coating material, and to improve the mechanical properties and barrier properties of the paper-based material while simplifying the processing technology.
[0007] To achieve the above objectives, in a first aspect, the present technical solution provides a method for preparing a paper-based high-performance environmentally friendly coating, comprising the following steps: The pH value of the nanocellulose solution is adjusted to 6.5-7.5, and the solution is diluted to a clear and colloid-free state, and pulp fibers are added to the diluted nanocellulose solution to obtain a mixed system; The mixed system is dehydrated to obtain a paper-based high-performance environmentally friendly coating material.
[0008] It should be noted that this scheme uses nanocellulose CNFs to improve the mechanical properties and barrier properties of pulp fibers. However, unlike the traditional process of first forming pulp fibers into paper and then coating them, this scheme directly dehydrates the nanocellulose solution and pulp fibers after blending to obtain a paper-based high-performance environmentally friendly coating material. The advantage of this is that it can avoid a series of problems caused by post-coating in the traditional process: 1) No requirements for CNF viscosity and concentration: CNF needs to be diluted and dispersed and pulp fiber compounded to obtain a mixed system before one-step papermaking filtration, so both high-concentration and low-concentration CNF can be used; 2) Simplified process flow: After uniform blending, only one step of papermaking and filtration is required to achieve the formation of the coating; 3) Achievement of high-quality coating: One-step filtration ensures uniform and stable coating; 4) Reduce energy consumption: Only one step of papermaking and filtration is required, and the integrated CNF / pulp papermaking system during the drying process avoids the different internal stresses of multiple layers of materials in the traditional drying process, which leads to the poor shrinkage of the paper substrate, and the mechanical properties of the finished paper are guaranteed.
[0009] The reason why nanocellulose in the nanocellulose solution can act as a reinforcing agent is that nanocellulose has a very high specific surface area and is charged, which allows nanocellulose to be effectively adsorbed on the surface of pulp fibers like traditional polyelectrolyte reinforcing agents, increasing their contact and bonding area, while the retained natural hemicellulose component can effectively solve the problem of compatible bonding between nanocellulose and pulp fibers. In addition, nanocellulose can also fill the tiny gaps between pulp fibers, and the long chain structure of nanocellulose can act as a physical bridge between fibers, which allows nanocellulose to also act as a rigid filler and help form a favorable network structure.
[0010] Based on the above characteristics of nanocellulose, nanocellulose can simultaneously form a thin film on the surface of the pulp substrate to improve the barrier properties of the paper-based material, and fill the inside of the paper-based material to improve the mechanical properties of the pulp substrate; however, considering that the cost of nanocellulose is much higher than that of pulp fiber, the post-coating method in the current processing technology requires repeated coating and drying, which will cause waste of nanocellulose. At the same time, the current processing technology is not only complicated but may also destroy the performance of the formed pulp substrate.
[0011] Based on this, the application team discovered through research that when the nanocellulose is first diluted and dispersed to obtain a nanocellulose solution and then blended with a pulp fiber solution, and the pH value of the nanocellulose solution is controlled to be neutral, the mixed system can be dehydrated to obtain a high-performance paper-based material with both barrier properties and mechanical properties.
[0012] This scheme can use one or any combination of mechanical, chemical, and biological methods to dilute and disperse nanocellulose to a clear, colloid-free state. When using the mechanical method to dilute and disperse nanocellulose, one of high-speed dispersion, cell disruption, ball milling, and ultrasonic treatment can be used; when using the chemical method to dilute and disperse nanocellulose, one of hydrolysis and oxidation methods can be used; when using the biological method to disperse nanocellulose, biological enzymes can be selected.
[0013] In a specific embodiment, a high-speed disperser or a cell disruptor at 850-10000 rpm is used for dispersion for 10 minutes until the mixture is clear and free of colloid.
[0014] It should be noted that this solution requires diluting and dispersing the nanocellulose solution until it reaches a clear, colloid-free state. The reason why the process of first diluting and dispersing the nanocellulose and then compounding it with pulp fibers to obtain a mixed system is adopted is that such a process is suitable for the treatment of any high or low concentrations of nanocellulose. Specifically, whether it is a high concentration or a low concentration of nanocellulose, it can be diluted to a suitable concentration with deionized water and then dispersed to obtain a nanocellulose solution, and then the nanocellulose solution is blended with the pulp fiber solution after decomposition. At this time, the dispersed nanocellulose can disperse the pulp fibers. On the one hand, due to the natural compatibility of CNF and pulp fibers, this dispersion step is conducive to promoting the combination of CNF and pulp fibers. On the other hand, the high charge of CNF itself makes the presence of CNF more conducive to the stable dispersion of pulp fibers in the solution. On the contrary, if a high-concentration nanocellulose solution is directly added to the pulp fiber solution for simple dilution, this will lead to uneven dispersion of the nanocellulose and the existence of local high-concentration areas, which will affect the subsequent dehydration application effect. This is because the high aspect ratio of nanocellulose makes its specific surface area large and there are a large number of hydrogen bonds between the fibers. The strong intermolecular force easily causes the nanocellulose to exist in the pulp fiber in the form of agglomerates. If the pulp fiber solution is used to disperse the nanocellulose, the penetration of water molecules cannot destroy the aggregates formed by the nanocellulose, which will lead to an uneven solution of the mixed system of nanocellulose and pulp fibers, which will easily affect the subsequent paper morphology and performance.
[0015] In some preferred embodiments, the concentration of the diluted nanocellulose solution is <0.2 wt %.
[0016] In some embodiments, the present solution uses any one or a combination of processes such as deionized water washing, acid neutralization, and alkali neutralization to adjust the pH value of the nanocellulose solution to 6.5-7.5, and as close as possible to the neutral condition of pH 7, so that the pH value of the mixed system obtained after the nanocellulose solution and the pulp fiber solution are blended is also biased towards the neutral condition. In other words, preferably, the nanocellulose solution is adjusted to a neutral pH value by using any one or a combination of processes such as deionized water washing, acid neutralization, and alkali neutralization.
[0017] In the preferred embodiment, the reason why the pH of the mixed system is adjusted to 6.5-7.5 is that from the product perspective of paper-based materials, a suitable charge density on the fiber surface can be maintained in a neutral pH environment. If the mixed system is too acidic, the fiber surface will have a low charge density in the form of carboxyl groups. If the mixed system is too alkaline, the fiber surface will be over-ionized, further affecting the performance of the fiber itself. From the perspective of the manufacturing process, whether the pH environment is too acidic or too alkaline, it may cause corrosion of the filter membrane and the preparation equipment. In the actual production process, the advantage of a neutral pH value is that the filtrate does not require additional chemicals for neutralization, which reduces the post-treatment process of the tail liquid.
[0018] In some embodiments, pulp fibers are beaten, and then the nanocellulose solution and the pulp fiber solution are mixed to obtain a mixed system. Beating refers to the process of mechanically treating fibers in an aqueous medium, which mainly causes internal fiberization of the fibers, enhances fiber flexibility, increases specific surface area, and increases hydrogen bonding points between fibers, which helps to enhance the mechanical properties of the finished paper.
[0019] In a specific embodiment, the CNFs obtained by the reaction are first diluted by adding deionized water, and the nanocellulose solution is obtained by using an Ultra-turrax homogenizer at 12000 rpm for 10 min. At this time, the pH of the nanocellulose solution is neutral, and then the pulp board is deflaked by a deflaker to obtain a pulp fiber solution, and finally the nanocellulose solution and the pulp fiber solution are mixed and stirred magnetically for 5 min to obtain a mixed system. This scheme is applicable to the treatment of various nanocelluloses, and the nanocellulose is selected from one or more of enzymatic nanocellulose, peroxyacid oxidized cellulose nanofibers, TEMPO oxidized cellulose nanofibers, carboxymethylated cellulose nanofibers, periodate oxidized cellulose nanofibers, maleic anhydride esterified cellulose nanofibers, phosphorylated cellulose nanofibers, and quaternized cellulose nanofibers. It should be noted that due to the different characteristics of different nanocelluloses themselves, the corresponding dilution and dispersion means are different.
[0020] In addition, the applicant team found that different nanocellulose sizes, surface properties and composition contents will affect the final high-performance pulp-based materials. In the embodiments of this scheme, the nanocellulose in the nanocellulose solution has a diameter of <30nm, a charge of >100μmol / L, and an aspect ratio of >100.
[0021] In a preferred embodiment, the present applicant team specially selects nanocellulose with a size of 2-30 nm, a charge of 100-2000 μmol / L, a hemicellulose content of 10%-25%, and an aspect ratio greater than 100 to prepare a nanocellulose solution. When such a nanocellulose solution is blended with pulp fibers to obtain a mixed system, part of the nanocellulose can automatically form a coating at the bottom of the pulp fibers, and the remaining part of the nanocellulose automatically fills the pulp fibers and combines with the pulp fibers, thereby forming a stable nanocellulose coating with certain barrier properties, while improving the tensile strength and elastic modulus of the paper-based material.
[0022] Regarding the size between 2 and 30 nm: The application team found that if the size of the nanocellulose is too large, it will be difficult for the nanocellulose to penetrate the wet filter cake formed by the pulp fibers during the filtration process, and it will be difficult to form a uniform and dense nanocellulose coating, resulting in a poor barrier effect of the final pulp-based material; on the contrary, if the size of the nanocellulose is too small, the nanocellulose will easily penetrate the wet filter cake formed by the pulp fibers during the filtration process. Although a barrier coating with a good barrier effect will be formed, it will greatly affect the filtration time on the one hand, and on the other hand, it will reduce the content of nanocellulose combined with the pulp fibers, resulting in the failure to improve the mechanical properties of the paper-based material.
[0023] Regarding the choice of charge between 100~20000μmol / L: When the charge of nanocellulose is too low, the nanocellulose will be unstable and unable to be well fibrillated, resulting in the nanocellulose being too large in size. At the same time, the formed nanocellulose coating will be more hydrophilic, resulting in the failure to significantly improve the barrier properties of the final paper-based material. However, there is sufficient repulsion between the nanofibers of nanocellulose with high charge, making its solution more stable. This repulsion can prevent the aggregation and precipitation of nanocellulose fibers, thereby extending the service life of the solution. At the same time, nanocellulose with high charge can more easily form a cross-linking system, which has great potential in applications such as reinforcement and coating stabilization.
[0024] Regarding the choice of hemicellulose content between 10% and 25%: The content of hemicellulose mainly affects the binding ability of the added nanocellulose and pulp fibers. Hemicellulose can be used as a binder to increase the binding rate of nanocellulose and pulp fibers. When the hemicellulose content is too low, on the one hand, it will reduce the binding of nanocellulose and pulp fibers, resulting in reduced mechanical properties of the final paper-based material. On the other hand, it means that the nanocellulose is strongly treated during the preparation process and more hemicellulose is lost. At this time, only smaller nanocellulose can be formed. If the size is too small, there will be a problem of nanocellulose easily penetrating the pulp fibers during the filtration process to form a wet filter cake. On the contrary, if the hemicellulose content is too high, it means that the nanocellulose is not sufficiently microfibrillated, and the size of the obtained nanocellulose is too high, which is not conducive to the formation of a nanocellulose coating.
[0025] In some embodiments, the mass ratio of nanocellulose in the nanocellulose solution to the mixed system is greater than 0.5wt%. The reason why this solution controls this mass ratio is that too low an amount of nanocellulose added is difficult to maintain the formation of a nanocellulose coating on the surface.
[0026] In addition, in some embodiments, the process for dehydrating the mixed system is selected from any one or a combination of processes of vacuum filtration, reduced pressure filtration, pressing, papermaking, paper pouring or drainage of the mixture.
[0027] In some embodiments, when vacuum filtration is adopted, the mixed system is subjected to vacuum filtration with a vacuum degree of -0.1MPa under the condition that the absolute pressure is close to 0. Specifically, in some embodiments, the mixed system is placed in a filtration device and the filtration conditions are set for filtration, wherein the filtration device includes a filtration part and a vacuum pump, wherein. The filtration part is sequentially a filter cup, filter paper, filter element and a triangular liquid collecting bottle from top to bottom, and the device connection of different components is sealed with a fixing clip and a sealing film, and finally the filtration part and the vacuum pump are connected by a pipeline. Of course, when this scheme performs one-step filtration on the mixed system, the filtration time is related to the system of the mixed system. Generally speaking, a 300mL mixed system requires 6 to 10 minutes to complete the filtration of a filter cake, and the specific time is affected by the objective filter element.
[0028] In some embodiments, when drainage is used, the mixed system is dehydrated at a water flow rate in a properly set drainage channel.
[0029] In some embodiments, when papermaking is adopted, the mixed system is evenly spread on a special papermaking net. With the help of the filtering and draining function of the papermaking net, part of the water seeps out through the mesh holes under the action of gravity. At the same time, by performing appropriate operations on the papermaking net (such as vibration, etc.), the water discharge can be further promoted, so that the fibers gradually form a paper prototype and achieve dehydration.
[0030] In some embodiments, when squeezing is used, a certain pressure is applied to squeeze out the remaining water in the mixed system through the pressure effect.
[0031] It should be noted that this scheme emphasizes the one-step dehydration treatment of the mixed system to obtain a paper-based high-performance environmentally friendly coating material. In other words, only one dehydration treatment is required to obtain a paper-based high-performance environmentally friendly coating material.
[0032] It should be noted that the present scheme can make the mixed system automatically stratified when dehydrating the mixed system. Part of the nanocellulose, due to its nanoscale size, can easily penetrate the pulp fibers during the filtration process to reach the bottom of the pulp fibers to form a dense nanofiber layer as a barrier coating; the remaining part of the nanocellulose, due to its high aspect ratio (greater than 100) and natural hemicellulose structure on the surface, can easily combine with the pulp fibers during the filtration process and be retained inside the pulp fibers as a reinforcing agent to improve the mechanical properties of the final high-performance paper-based material.
[0033] In addition, in some embodiments, the mixed system is dehydrated and then dried to obtain a paper-based high-performance environmentally friendly coating material, and the drying method after dehydration can be selected from any one of vacuum drying, freeze drying, natural air drying, and hot pressing drying. Preferably, this solution selects the hot pressing drying method.
[0034] In order to avoid the situation where the filtration cannot achieve complete drying, this solution uses an additional drying method after filtration to help paper forming. The hot press drying method is specially selected to make the paper more compact.
[0035] In the second aspect, the present scheme provides a paper-based high-performance environmentally friendly coating material, which is prepared according to the preparation method of a paper-based high-performance environmentally friendly coating material mentioned in the first aspect. A nanocellulose coating is formed on the bottom of the paper-based high-performance environmentally friendly coating material, and the internal pulp fibers are bonded by nanocellulose.
[0036] In some embodiments, the paper-based high-performance environmentally friendly coating material has good barrier properties, and the water contact angle of the barrier surface of the nanocellulose coating of the paper-based high-performance environmentally friendly coating material is increased by more than 60°, and the oil resistance KIT>10.
[0037] In some embodiments, the paper-based high-performance environmentally friendly coating material has good mechanical properties. The Young's modulus of the nanocellulose coating of the paper-based high-performance environmentally friendly coating material is increased by nearly 50% and the tensile breaking strength is increased by nearly 60% compared to the pure paper-based material.
[0038] Compared with the prior art, this technical solution has the following characteristics and beneficial effects: The present invention provides a paper-based high-performance environmentally friendly coating material and a preparation method thereof. The preparation method innovates the traditional method of first forming paper and then coating. The method first disperses a nanocellulose solution and then blends it with a pulp cellulose solution to obtain a neutral mixed system. The mixed system is then subjected to a dehydration treatment process to automatically layer the system to obtain a high-performance paper-based material. A nanocellulose coating is formed on the bottom of the paper-based high-performance environmentally friendly coating material, and the pulp fibers inside are combined with the nanocellulose. During the dehydration process, part of the nanocellulose penetrates the pulp fibers to reach the bottom to form a nanocellulose coating, and the other part of the nanocellulose is combined with the pulp fibers, thereby achieving a simultaneous improvement in barrier properties and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the microstructure of the high-performance pulp material containing nanocellulose coating prepared in Example 1.
[0040] Figure 2 Actual picture of the surface of the high-performance pulp material containing nanocellulose coating prepared in Example 1 after testing of water contact angle and oil resistance.
[0041] Figure 3 Example 1, Example 10 to Example 13, surface performance diagrams of high-performance pulp materials containing nanocellulose coatings prepared at different nanocellulose addition ratios.
[0042] Figure 4 Example 1, Example 10 to Example 13, mechanical properties diagrams of high-performance pulp materials containing nanocellulose coatings prepared at different nanocellulose addition ratios.
[0043] Figure 5 This is a process flow chart of the present invention for preparing high-performance pulp materials containing nanocellulose coating. DETAILED DESCRIPTION
[0044] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0045] It is to be understood that the term "one" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element may be one, while in another embodiment, the number of the element may be multiple, and the term "one" should not be understood as a limitation on the quantity.
[0046] In order to verify the performance of the high-performance paper-based material of this scheme, this scheme designs the following embodiments: Embodiment 1 Preparation of nanocellulose solution: Using white pine as raw material, the wood was cut into pieces about 3 cm long along the extension direction of the plant fiber, immersed in 4 wt% peracetic acid, and the pH of the system was adjusted to 4.5 using 20 wt% sodium hydroxide solution. After heating the reaction at 85 °C for 1 h, the solid fiber product was immersed in 4 wt% peracetic acid again, and the above process was repeated until the fiber was white. The sample was filtered with 250 mesh gauze, and the fiber sample was repeatedly washed with a large amount of deionized water until the filtrate was neutral. The final sample mainly contained cellulose and hemicellulose. The fiber was further fibrillated by rapid mechanical stirring and shearing using a high-speed wall breaker to obtain a nanocellulose solution. The size of the nanocellulose in the nanocellulose solution was 3 nm, the charge was 400 μmol / L, the hemicellulose content was 20%, and the addition ratio of nanocellulose was 7.0 wt%; Dispersing nanocellulose solution: Disperse nanocellulose in water and use a high-speed disperser at 10,000 rpm for 10 minutes until it is clear and free of colloid.
[0047] Preparation of pulp fiber solution: Use pulp board as raw material, cut into small pieces and use a deflaking machine to deflake to obtain dispersed pulp fiber solution, squeeze and store for use. Weigh a certain amount of pulp fiber according to the solid content. The paper base weight is 80g / m 2 .
[0048] Preparation of a mixed system: adding weighed pulp fibers to the dispersed nanocellulose solution, dispersing the mixed solution under magnetic stirring to obtain a mixed system, and controlling the addition ratio of the nanocellulose solution to the pulp fiber solution to be 5:80.
[0049] Dehydration to obtain high-performance paper-based materials: The mixed system is placed in a filtration device built in the laboratory, the vacuum degree is controlled at -0.1MPa, and a paper-based high-performance environmentally friendly coating material is obtained by filtration once.
[0050] Embodiment 2 In order to verify the effect of the dispersion order of nanocellulose and pulp fibers on the final high-performance paper-based material, Example 2 was designed in which pulp fibers were first dispersed and then blended with nanocellulose, and other conditions were the same as Example 1. In other words, Example 2 did not disperse the nanocellulose solution but directly blended it with the pulp fiber solution, and other processes were the same.
[0051] Embodiment 3 to Embodiment 4: In order to verify the effect of the pH value of the mixed solution on the final high-performance paper-based material, the pH value of the mixed system is designed to be different from that of Example 1 in Example 3 to Example 4, and the other conditions are the same as in Example 1. The conditions of Example 3 to Example 4 are as shown in Table 1 below: Table 1 Conditions of Example 3 and Example 4 .
[0052] Embodiment 5 In order to verify the effect of the pulping process on the final high-performance paper-based material, Example 5 is designed to perform decomposition and pulping by placing the pulp fibers into a pulper during decomposition and using mechanical action to treat the pulp fibers suspended in water. Other conditions are the same as those in Example 1.
[0053] Embodiment 6 to Embodiment 9 In order to verify the influence of nanocellulose size, surface charge and hemicellulose content on the final high-performance paper-based material, nanocellulose under different preparation processes was designed, and its performance was different from that of Example 1 in Example 6 to Example 4, and other conditions were the same as in Example 1. The conditions of Example 6 to Example 9 are as follows in Table 2: Table 2 Nanocellulose of Examples 6 to 9
[0054] Embodiment 10 to Embodiment 11: In order to verify the effect of the addition ratio of nanocellulose on the final high-performance paper-based material, the addition amount of nanocellulose is designed to be different from that of Example 1 in Example 10 to Example 13, and the other conditions are the same as in Example 1. The conditions of Example 10 to Example 13 are as shown in Table 3 below: Table 3 Conditions of Examples 6 to 9 .
[0055] Performance Test: 1. Morphology observation: The material morphology was observed using a field emission scanning electron microscope (SEM, SU-8010) on the test platform of the State Key Laboratory of Chemical Engineering (Zhejiang University). The morphology of the high-performance paper-based material obtained in Example 1 is shown in the figure below. Figure 1 As shown, you can see Figure 1 A nanocellulose coating is formed on the bottom of the high-performance paper-based material, and the pulp fibers inside are cross-linked.
[0056] 2. Surface barrier performance test: The paper-based materials obtained in Example 1, Example 6 to Example 9 were tested for barrier properties. (1) Water contact angle: The static water contact angle of the material was measured using the video optical contact angle meter (OCA 20) at the testing platform of the State Key Laboratory of Chemical Engineering (Zhejiang University).
[0057] (2) Oil resistance (KIT value): Oil resistance is measured by the KIT test according to TAPPI T 559 method. KIT solution is made by mixing n-heptane, toluene and castor oil. KIT 1 and KIT 12 represent the weakest and strongest oil resistance, respectively.
[0058] The test results are as follows Figure 2 As shown, it can be seen that the barrier surface of the paper-based material of Example 1 provides a certain degree of hydrophobicity (water contact angle WCA>60º) and excellent oil resistance (KIT>10). This is because in Example 1, a dense CNF film is formed on the surface of the paper-based material to coat the porous surface of the original paper-based material. At the same time, the CNF and pulp fibers inside the material are tightly entangled, and the CNF fills the pores of the original paper-based material. Therefore, small molecules such as water and oil need to go through a longer path to penetrate the material, so that the paper-based material obtained in Example 1 has excellent water-blocking, oil-blocking and air-blocking properties. In addition, the test results of the barrier properties of the paper-based materials of Example 1, Example 6 to Example 9 are shown in Table 4 below.
[0059] Table 4 Test results of barrier properties of paper-based materials in Example 1, Example 6 to Example 9 .
[0060] 3. Performance test: Cut a 25 mm long and 5 mm wide strip, install it on a universal material testing machine, adjust the tensile rate to 2.5 mm / min to measure the mechanical properties of the sample, and the test results of Example 1 and Example 6 to Example 9 are shown in Table 5. It can be seen that at the same amount of nanocellulose added, the mechanical properties of the paper-based material of Example 1 are significantly improved. Compared with the pure paper-based material, the Young's modulus is increased by nearly 200%, and the tensile breaking strength is increased by nearly 240%. This is because in Example 1, in the material of this technology, the CNF forming the surface coating can coat the porous surface of the original paper-based material, and at the same time, the residual CNF and pulp fibers inside are tightly entangled to form a dense and stable network structure, which is conducive to the improvement of the mechanical properties.
[0061] Table 5 Test results of mechanical properties of paper-based materials obtained in Example 1, Example 6 to Example 9 .
[0062] 4. Add ratio optimization analysis: The surface barrier properties and mechanical properties of the papers obtained in Examples 10 to 13 were analyzed. Figure 3 and Figure 4 It can be seen that with the gradual increase in the amount of nanocellulose added, the surface properties of the finished paper tend to be stable, and the mechanical properties show a trend of first increasing and then decreasing. This is because too much nanocellulose will agglomerate internally to form tensile weaknesses. The addition ratio of 3.5wt%-10.5wt% can produce paper with excellent performance.
[0063] 5. Process sequence optimization analysis: KIT value analysis and tensile strength analysis were performed on Example 1 and Example 2. The analysis method was as above. The results are shown in Table 6. It can be seen that the tensile strength of the paper-based material obtained in Example 1, in which the nanocellulose is first dispersed and then blended with the pulp fiber solution, is significantly better than that in Example 2. From the KIT value of the paper-based material of Example 2, it can be clearly seen that only when the nanocellulose is first dispersed and then blended with the pulp fiber solution can a high-performance paper-based material with a layered structure be formed.
[0064] Table 6 Performance test of embodiment 1 and embodiment 10 .
[0065] 7. Optimization analysis of pH value of mixed solution: KIT value analysis and tensile strength analysis were performed on Example 1, Example 3 and Example 4, and the zeta potential test of nanocellulose was additionally performed. The results are shown in Table 7: Table 7 Performance test of embodiment 1, embodiment 3 and embodiment 4 .
[0066] It can also be seen from the KIT values of Example 3 and Example 4 that a high-performance paper-based material with good stratification properties can be formed only when the pH value of the nanocellulose solution is neutral.
[0067] 8. Analysis on optimization of pulping process: KIT value analysis and tensile strength analysis were performed on Example 1 and Example 5, and the analysis methods were the same as above. The results are shown in Table 8, which shows that the tensile strength of the paper-based fibers after pulping can be further optimized.
[0068] Table 8 Performance test of embodiment 1 and embodiment 11 .
[0069] 8. Recyclability test: Three commercial barrier papers were selected and soaked, dispersed, pulped and made into paper under the same storage fried chicken conditions as the paper obtained in Example 1 of this scheme. The recycling performance of these three commercial barrier papers is much worse, and large aggregates will still remain after the re-pulping process, which will cause large defects in the paper. This is because the coating materials of these commercial barrier papers cannot be decomposed in water, and other additives (i.e., reinforcing additives) may be used to bond the pulp fibers in an irreversible manner. Under this technology, the paper can be easily (using a simple 600 rpm magnetic stirring) re-pulped (decomposed) into pulp fibers with minimal aggregates, and the final paper has a uniform appearance and good mechanical properties.
[0070] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.
Claims
1. A method for preparing a paper-based high-performance environmentally friendly coating, characterized in that: The following steps are involved: The pH value of the nanocellulose solution is adjusted to 6.5-7.5, and the solution is diluted to a clear and colloid-free state, and pulp fibers are added to the diluted nanocellulose solution to obtain a mixed system; The mixed system is dehydrated to obtain a paper-based high-performance environmentally friendly coating material.
2. The method for preparing a paper-based high-performance environmentally friendly coating according to claim 1, characterized in that: The nanocellulose is selected from one or more of enzymatic nanocellulose, peroxyacid oxidized cellulose nanofibers, TEMPO oxidized cellulose nanofibers, carboxymethylated cellulose nanofibers, periodate oxidized cellulose nanofibers, maleic anhydride esterified cellulose nanofibers, phosphorylated cellulose nanofibers, and quaternized cellulose nanofibers.
3. The method for preparing a paper-based high-performance environmentally friendly coating according to claim 1, characterized in that: The diameter of nanocellulose in the nanocellulose solution is < 30 nm, the charge is >100 μmol / L, and the aspect ratio is >100.
4. The method for preparing a paper-based high-performance environmentally friendly coating according to claim 1, characterized in that: The pH value of the nanocellulose solution is adjusted to 6.5-7.5 by any one or a combination of processes such as deionized water washing, acid neutralization, and alkali neutralization.
5. The method for preparing a paper-based high-performance environmentally friendly coating according to claim 1, characterized in that: The concentration of the diluted nanocellulose solution was < 0.2 wt%.
6. The method for preparing a paper-based high-performance environmentally friendly coating according to claim 1, characterized in that: The pulp fibers are beaten, and then the nanocellulose solution and the pulp fibers are mixed to obtain a mixed system.
7. The method for preparing a paper-based high-performance environmentally friendly coating according to claim 1, characterized in that: The mass ratio of nanocellulose in the nanocellulose solution to the mixed system is > 0.5 wt%.
8. The method for preparing a paper-based high-performance environmentally friendly coating according to claim 1, characterized in that: The process for dehydrating the mixed system is selected from any one or a combination of processes of vacuum filtration, reduced pressure filtration, pressing, papermaking, paper pouring or drainage of the mixed body.
9. A paper-based high-performance environmentally friendly coating material, characterized in that: The paper-based high-performance environmentally friendly coating material is prepared according to the preparation method of any one of claims 1 to 8, wherein a dense coating of nanocellulose is formed on the bottom of the paper-based high-performance environmentally friendly coating material, and the internal pulp fibers are bonded by nanocellulose.
10. The paper-based high-performance environmentally friendly coating material according to claim 9, characterized in that: The water contact angle of the barrier surface of the nanocellulose coating of the paper-based high-performance environmentally friendly coating material is increased by > 40°, the oil resistance KIT value is increased by > 8, the Young's modulus is increased by > 50% compared to pure paper-based materials, and the tensile breaking strength is increased by > 60%.
Citation Information
Patent Citations
High aspect ratio cellulose nanofilaments and method for production thereof
CN103502529A
Preparation method of modified impregnated paper body paper
CN104894914A
Stacking-assembled reinforced paper base as well as preparation method and application thereof
CN107524043A
Paper and preparation method and application thereof
CN110130150A
Preparation method of high-transparency and high-barrier cellulose paper
CN113152150A